Spectrophotometric Determination of Aspirin in Pure Form and Pharmaceutical Formulations using Oxidation–reduction reaction - Ayad M.R. Raauf; Huda Mohammed; Ali Wathiq Alwan Ajil (Al-Mustansiriyah Journal of Pharmaceutical Sciences, 2010)
A simple, sensitive and accurate spectrophotometric method of determination of aspirin in pure form and pharmaceutical formulation. The method is based on the formation of Prussian blue (PB) complex. The reaction between the acidic hydrolysis product of the aspirin with the mixture of FeCl3 and potassium hexacyanoferrate (ΙΙΙ) was evaluated for the spectrophotometric determination of the aspirin. The maximum absorbance of the colored complex occurred at λ=765nm. Reaction conditions have been optimized to obtain PB complex of high sensitivity and longer stability. Under optimum conditions the absorbance of the PB complex where found to increase linearly with increase in concentration of the aspirin, which corroborated with correlation coefficient value. The concentration ranges are 0.5-7μg mL-1 with detection limit 0,2267μg mL-1 and relative standard deviation 0,025%. The proposed method was successfully applied to determine of the selected aspirin in pure form and pharmaceutical formulations with good precision and accuracy compared to standard method as revealed by t- and F- values and the results obtained agree well with the labeled contents.